Penanganan Gangguan Gagal Balik Point Machine No. P1106 di Pocket Track LRT Jakarta Pada Saat Perawatan Menggunakan Metode FTA dan FMEA - Avrellita, Reinanda; Puspitasari, Mariana Diah; Oktaria, Dhina Setyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Point machine or drive on the wesel is one of the external equipment on the railroad system that functions to move one line to another. There are two types, mechanical and electrical. Jakarta LRT uses an electric vane drive with the Voestalpine product name with the Unistar HR EM type. There is often a back failure disturbance caused by point machine no P1106. This study aims to analyze the cause of the reverse failure. Using two analysis methods, namely Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). The results found that the cause of the reverse failure at point machine no P1106 is from the detection switch component that occurs bad contact due to corrosion with the form of sparks.